INCREASING THE EFFICIENCY OF GAS DISTRIBUTION STATION OP-ERATION IN CONDITIONS OF VARIABLE CAPACITY - Volianska, Larysa; Nikitina, Galyna; Ratynskyi, Valerii; Babichev, Ivan (Science-based technologies, 2024)
The article is devoted to the study of increasing the efficiency of gas distribution stations through modernization and technical re-equipment. The problem of efficient use of the potential energy of natural gas at gas distribution stations of gas supply systems is considered. The reduction in gas pressure during the transition from the main gas pipeline to the distribution system is carried out by throttling in the reduction unit of the gas distribution station. In this process, the potential energy of the gas is lost without doing any work. The article proposes to increase the efficiency of converting the potential energy of gas into electrical energy through the introduction of turboexpander units. By recycling systems based on turbo-expander electric generating units and aggregates, they simultaneously reduce and regulate gas pressure during its expansion in the machine, as well as obtain mechanical work on the shaft and convert it into electricity. Increasing the efficiency of gas distribution stations is possible by a complete modernization of the station if it is economically reasonable or using limited, low-cost measures to reconstruct individual components or the piping of the station. The article analyzes the increase in energy efficiency of technological processes of a gas distribution station by the use of low-cost measures. Identification of capacity reserves of a gas distribution station and reconstruction of individual sections of the station in order to increase capacity make it possible to use the station under conditions of increased load, i.e. ensure compliance with the design and operational performance of the gas distribution station. A mathematical model has been formed to study the gas flow in the gas pipeline of the reduction line after the gas pressure regulator and the boundary conditions for carrying out calculations have been established. Using a mathematical model, the gas flow in the reduction line after the pressure regulator valve was simulated under different operating conditions. A thermodynamic calculation of one of the options for a low-cost measure is given. Results are presented that confirm the possibility of utilizing the energy of compressed natural gas during the reduction process, even with high irregularity of gas selection by consumers.